Navigating the Digital Landscape: How Nahdlatul Ulama Volunteers Use Social Media for Organizational Promotion - Dony Arung Triantoro (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This article aims to investigate how the digital volunteers of Nahdlatul Ulama (NU) utilize social media to promote the organization. The study employs a qualitative approach, gathering data through online interviews and content analysis of the Instagram account @nucreativemedia. This study will address three questions: First, what motivates digital volunteers to create the Instagram account @nucreativemedia? Second, what types of content are promoted on this account? Third, how do digital volunteers present NU content on Instagram? Based on these questions, the findings indicate that: First, the initiative to create the Instagram account @nucreativemedia is driven by the desire to counter radical and conservative Islamic movements on social media. Second, the content promoted includes NU scholars, fiqh and worship, social-political issues, and public facilities associated with NU, such as pesantren (Islamic boarding schools), hospitals, universities, and products. Third, the Instagram account @nucreativemedia enhances its content through a combination of colors, images, and audio that reflect NU culture. This promotional effort further reinforces NU's position and relevance in the online space.